Medicine dispensing service in primary health care of SUS - Silvana Nair Leite; Noemia Liege Maria da Cunha Bernardo; Juliana Álvares; Augusto Afonso Guerra Junior; Ediná Alves Costa; Francisco de Assis Acurcio; Ione Aquemi Guibu; Karen Sarmento Costa; Margô Gomes de Oliveira Karnikowski; Orlando Mario Soeiro; Luciano Soares (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To characterize the medicine dispensing services in the primary health care network in Brazil and in its different regions, aiming to promote the access and rational use of medicines. METHODS This is a cross-sectional, quantitative study with data obtained from the Pesquisa Nacional sobre Acesso, Utilização e Uso Racional de Medicamentos (PNAUM - National Survey on Access, Use and Promotion of Rational Use of Medicines), 2015. Observation visits were carried out in 1,175 dispensing units, and interviews were held with 1,139 professionals responsible for the dispensation of medicines in the dispensing units and 495 municipal coordinators of pharmaceutical services. RESULTS More than half (53%) of the units presented a space smaller than 10 m2 for dispensing of medicines; 23.8% had bars or barriers between users and dispenser; 41.7% had computerized system; and 23.7% had counters for individual care. Among those responsible for dispensation, 87.4% said they always or repeatedly inform users how to use the medicines, and 18.1% reported developing some type of clinical activity. Isolated pharmacies presented a more developed physical and personal structure than those belonging to health units, but we found no significant differences regarding the information provided and the development of clinical activities. CONCLUSIONS There are major differences in the organization models of dispensation between cities, with regional differences regarding the physical structure and professionals involved. The centralization of medicine dispensing in pharmacies separated from the health services is associated with better structural and professional conditions, as in the dispensing units of the South, Southeast, and Midwest regions. However, the development of dispensation as health service does not prevail in any pharmacy or region of the Country yet.